Ten key messages of the guidelines for family-centered care in intensive care medicine - Petros, S.; John, Stefan (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2019)
The family plays an important role in the care of the critically ill patient. There is asubstantial psychological burden to family members during the intensive care management of the patient. The family has to bear the pitiable state of the patient with the feeling of helplessness. The critically ill patient is frequently unable to actively decide on the processes of intensive care. Therefore, the family has to take over the responsibility of representing the values and wishes of the patient and become involved in decision making, for which most family members are not prepared. Aconsiderable proportion of family members suffers from stress, anxiety and depression. This psychological burden also continues after the conclusion of the intensive care management. Therefore, structured approaches are needed to support family members of critically ill patients during the intensive care management. In this short review, we present the ten key messages of the recent guidelines for family-centered care in the intensive care unit by the Society of Critical Care Medicine.
CRIS-Team WoS Importer:2019-02-21